The significance of the influence of job satisfaction on the performance of nurses in psychiatric hospital - Saimi, Saimi; Khalik, Lalu Abdul; Menap, Menap; Hidayati, Fitria (Journal of Midwifery and Nursing, 2024)
This article investigate influence satisfaction Work to performance nurse at Mutiara Sukma Mental Hospital. Satisfaction Work nurse considered as response psychological and emotional to environment work, employment, and interpersonal relationships. Internal factors, such as evaluation to work and satisfaction to achievement personal, as well factor external, incl condition work and support organizational, yes influence satisfaction Work. Satisfaction Work nurses are also reflected in involvement in taking decisions and a sense of being valued by the organization. Study This aim for investigate connection between satisfaction work and performance home nurse Sick the. Study This involving 110 respondents who were nurse at Mutiara Sukma Mental Hospital. Data collection was carried out through assessment questionnaire level satisfaction work and performance nurse. Data analysis used the independent T test and simple linear regression. Research result show exists difference significant in performance between group satisfaction Work high and low. Analysis regression disclose connection significant positive _ between satisfaction work and performance nurse. In other words, more and more tall level satisfaction work, increasingly good performance too nurse. Findings This own implications practical in management source Power man at home Sick health soul. Management can use results study This as base for develop improving management policies and programs satisfaction Work nurse, with objective increase quality service mental health. With understand and improve satisfaction Work nurse , home Sick can reach service health optimal soul.